Investigation of orexin-2 selective receptor antagonists: Structural modifications resulting in dual orexin receptor antagonists. Issue 6 (15th March 2017) - Skudlarek, Jason W.; DiMarco, Christina N.; Babaoglu, Kerim; Roecker, Anthony J.; Bruno, Joseph G.; Pausch, Mark A.; O'Brien, Julie A.; Cabalu, Tamara D.; Stevens, Joanne; Brunner, Joseph; Tannenbaum, Pamela L.; Wuelfing, W. Peter; et al.
Graphical abstract: Abstract: In an ongoing effort to explore the use of orexin receptor antagonists for the treatment of insomnia, dual orexin receptor antagonists (DORAs) were structurally modified, resulting in compounds selective for the OX2 R subtype and culminating in the discovery of23, a highly potent, OX2 R-selective molecule that exhibited a promising in vivo profile. Further structural modification led to an unexpected restoration of OX1 R antagonism. Herein, these changes are discussed and a rationale for selectivity based on computational modeling is proposed.